The lucerne in Spain. Characterization of the cultivated and spontaneous ecotypes - Delgado Enguita I. (The Genus Medicago in the Mediterranean region: Current situation and prospects in research, 1996)
The aim of this work is to sum up the studies carried out on the characterization of the lucerne cultivated ecotypes and spontaneous ones by the Pasture and Forages Laboratory of the SIA-DGA in the last fifteen years. These studies show the similitude and differences of the Spanish cultivated ecotypes versus the Flemish, African or intermediate kinds of ecotypes. The spontaneous ecotypes present the morphological characteristics of spp. sativa but they produce rhizomes and their growing habit is similar to spp. falcata.
Meeting of the Mediterranean Working Group on Medicago of the FAO/CIHEAM Inter-Regional Research and Development Network on Pastures and Fodder Crops, 1995/10/19-22, Hammamet (Tunisia)